Dual‐Confined Sulfur Nanoparticles Encapsulated in Hollow TiO2 Spheres Wrapped with Graphene for Lithium–Sulfur Batteries. Issue 20 (14th September 2016) - Fan, Haining; Tang, Qunli; Chen, Xiaohua; Fan, Binbin; Chen, Shanliang; Hu, Aiping
Abstract: Lithium–sulfur (Li−S) batteries are attractive owing to their higher energy density and lower cost compared with the universally used lithium‐ion batteries (LIBs), but there are some problems that stop their practical use, such as low utilization and rapid capacity‐fading of the sulfur cathode, which is mainly caused by the shuttle effect, and the uncontrollable deposition of lithium sulfide species. Herein, we report the design and fabrication of dual‐confined sulfur nanoparticles that were encapsulated inside hollow TiO2 spheres; the encapsulated nanoparticles were prepared by a facile hydrolysis process combined with acid etching, followed by "wrapping" with graphene (G−TiO2 @S). In this unique composite architecture, the hollow TiO2 spheres acted as effective sulfur carriers by confining the polysulfides and buffering volume changes during the charge‐discharge processes by means of physical force from the hollow spheres and chemical binding between TiO2 and the polysulfides. Moreover, the graphene‐wrapped skin provided an effective 3D conductive network to improve the electronic conductivity of the sulfur cathode and, at the same time, to further suppress the dissolution of the polysulfides. As results, the G−TiO2 @S hybrids exhibited a high and stable discharge capacity of up to 853.4 mA h g −1 over 200 cycles at 0.5 C (1 C=1675 mA g −1 ) and an excellent rate capability of 675 mA h g −1 at a current rate of 2 C; thus, G−TiO2 @S holds great promise as a cathode material for Li−S batteries. Abstract : Sleepy hollow : Hollow TiO2 spheres acted as effective sulfur carriers by confining the polysulfides and buffering volume changes during charge–discharge processes by means of physical force from the hollow spheres and chemical binding between TiO2 and the polysulfides.